Ethics and professionalism in forensic anthropology Nicholas V. Passalacqua, Marin A. Pilloud. - Passalacqua, Nicholas V.; Pilloud, Marin A. (London, United Kingdom Academic Press, 2018)
"Forensic anthropologists are confronted with ethical issues as part of their education, research, teaching, professional development, and casework. Despite the many ethical challenges that may impact forensic anthropologists, discourse and training in ethics are limited. The goal for Ethics and Professionalism in Forensic Anthropology is to outline the current state of ethics within the field and to start a discussion about the ethics, professionalism, and legal concerns associated with the practice of forensic anthropology."--Back cover.
Includes bibliographic references (pages 121-129) and index.
Keywords: Forensic anthropology -- Moral and ethical aspects; Professional ethics